일방향 응고 니켈기 초내열 합금 CM247LC의 온도에 따른 크리프 특성 - 최백규; Baig-gyu Choi; 도정현; Jeonghyeon Do; 정중은; Joong Eun Jung; 석우영; Woo-young Seok; 이유화; Yu-hwa Lee; 김인수; In Soo Kim (한국주조공학회지, 2021)
일방향응고로 제조된 니켈기 초내열합금 CM247LC의 다양한 온도 및 응력조건에서 크리프 특성에 대해 고찰하였다. 열처리 후 일부 공정조직이 남아 있었으며 비교적 균일한 육면체의 γ'이 수지상 내부와 수지상간 영역에서 관찰되었다. 상대적 저온인 750℃의 고응력 크리프 영역에서는 1차 크리프 동안 많은 변형이 발생하였으나 고온으로 갈수록 3차 크리프 구간이 크리프 변형시간의 대부분을 차지함을 알 수 있었다. 저온 고응력에서는 부분 전위가 γ'으로 진입하며 적층결함을 γ'내에 생성시켰으며 초기 크리프변형속도가 증가하는 부분이 있었으나 850℃ 이상의 온도에서는 γ' 내부에서 적층결함이 관찰되지 않았으며 이는 적층결함에너지의 온도의존성 때문인 것으로 판단된다. 고온이어서 확산속도가 빠른 950℃와 1000℃에서는 γ'의 래프팅이 관찰되었다. 온도가 좀 더 낮은 850℃에서는 변형기구가 응력에 따라 다르게 나타나서 상대적으로 크리프 시간이 긴 저응력에서만 래프팅이 관찰되었다. Creep properties of directionally solidified Ni-based superalloy CM247LC under various temperature and stress conditions have been investigated. In the heat-treated specimen, some portion of eutectic γ-γ' remained, and uniform cubic γ' was observed in the dendrites. At low temperature (750℃) and high stress condition, a large amount of deformation occurred during the primary creep, while the tertiary creep region accounted for most of the creep deformation under high temperature and low stress condition. γ' particles are sheared by dislocation dissociated into super lattice partial dislocations separated by stacking faults at 750℃. No stacking faults in γ' were found at and above 850℃ due to the temperature dependence of the stacking fault energy. Raft structure of γ' was found after creep test at high temperature of 950℃ and 1000℃. At 850℃, the deformation mechanism was shown to be dependent on the stress condition, and so rafting was observed only under low stress condition.